The Paradox of Democratic Media: Platform Logic and the Failure of Policy Conversion in Indonesia's 17+8 Movement - Alif Firdaus Zamzam; Nurul Laili (Universitas Islam Darul Ulum Lamongan, 2026)
Indonesia witnessed an unprecedented wave of nationwide mass mobilization driven by widening disparities between the privileges enjoyed by political elites and the mounting economic pressures faced by lower- and middle-income communities. This mobilization was further amplified by the rapid circulation of digital narratives across social media platforms. This article examines the movement's central paradox: its remarkable capacity to rapidly consolidate cross-class demands was accompanied—not proportionally, but simultaneously—by its inability to translate those demands into binding public policy. This study employs a qualitative literature review approach combined with digital discourse analysis of publicly circulated social media content collected during the escalation of the movement and the subsequent post-deadline monitoring period. The analysis proceeds through three stages: mapping the movement's action-network structure, tracing the declining visibility of campaign hashtags over time, and interpreting the findings through the theoretical framework of paradoxical democracy. The findings demonstrate that the 17+8 Movement represents a prototype of a crowd-enabled action network operating without a formal brokering organization. While this decentralized structure enabled rapid mass mobilization, it also rendered the movement highly vulnerable to digital repression and algorithmic shifts in public attention once the viral momentum subsided. Consequently, the movement's failure to achieve policy conversion should not be interpreted as evidence of the ineffectiveness of digital activism itself. Rather, it reflects a structural failure of policy conversion, arising from a digital ecosystem that remains insufficiently connected to institutional channels capable of transforming civic participation into formal political outcomes before public attention shifts toward competing issues.